Physiological and Biological Responses to Short-Term Intermittent Hypobaric Hypoxia Exposure: From Sports and Mountain Medicine to New Biomedical Applications - Viscor, Ginés; Torrella, Joan R.; Corral, Luisa; Ricart, Antoni; Javierre, Casimiro; Pages, Teresa; Ventura, Josep L. (Frontiers in Physiology, 2018)
In recent years, the altitude acclimatization responses elicited by short-term intermittent exposure to hypoxia have been subject to renewed attention. The main goal of short-term intermittent hypobaric hypoxia exposure programs was originally to improve the aerobic capacity of athletes or to accelerate the altitude acclimatization response in alpinists, since such programs induce an increase in erythrocyte mass. Several model programs of intermittent exposure to hypoxia have presented efficiency with respect to this goal, without any of the inconveniences or negative consequences associated with permanent stays at moderate or high altitudes. Artificial intermittent exposure to normobaric hypoxia systems have seen a rapid rise in popularity among recreational and professional athletes, not only due to their unbeatable cost/efficiency ratio, but also because they help prevent common inconveniences associated with high-altitude stays such as social isolation, nutritional limitations, and other minor health and comfort-related annoyances. Today, intermittent exposure to hypobaric hypoxia is known to elicit other physiological response types in several organs and body systems. These responses range from alterations in the ventilatory pattern to modulation of the mitochondrial function. The central role played by hypoxia-inducible factor (HIF) in activating a signaling molecular cascade after hypoxia exposure is well known. Among these targets, several growth factors that upregulate the capillary bed by inducing angiogenesis and promoting oxidative metabolism merit special attention. Applying intermittent hypobaric hypoxia to promote the action of some molecules, such as angiogenic factors, could improve repair and recovery in many tissue types. This article uses a comprehensive approach to examine data obtained in recent years. We consider evidence collected from different tissues, including myocardial capillarization, skeletal muscle fiber types and fiber size changes induced by intermittent hypoxia exposure, and discuss the evidence that points to beneficial interventions in applied fields such as sport science. Short-term intermittent hypoxia may not only be useful for healthy people, but could also be considered a promising tool to be applied, with due caution, to some pathophysiological states.